Effects of Diversified Sports Activity Module on Physical Fitness and Mental Health of 4-5-Year-Old Preschoolers - Jinfu Liu; Feng Gao; Lugang Yuan (Tehran University of Medical Sciences, 2021)
Background: Chinese children are poorer in sports activity as compared to foreign children and their prospects as to physical fitness are not optimistic. This study aimed to discuss the effects of diversified sports activity modules on physical fitness and mental health of preschoolers ages 4-5 years. Methods: Sixty preschoolers aged 4-5-yr-old from two kindergartens in Jiaxing of China were selected randomly during Mar-Oct 2019. These respondents were divided into the experimental group (n=30) and the control group (n=30). The experimental group implemented the diversified sports activity module for 16 wk successively, 5 d per week, and 30-45 min per day. The control group adopted conventional sports activity. The body shape, physical fitness, and mental health of the two groups were measured and compared. Results: For body shape, the height of the experimental group increased is significantly higher than that of the control group. The experimental and control groups show no significant differences in body weight. For physical fitness, the experimental group is significantly superior to the control group in testing results of standing long jump, double-feet continuous jump, balancing on one foot, tennis shot, sit-and-reach, and 10 m repeated run. For mental health, the testing results of action development, language development, and social development of the experimental group are significantly better than those of the control group. Conclusion: The diversified sports activity module is not only conducive to strengthening the physical fitness of 4-5-year-old preschoolers but also improves their mental health.